TURQUALITY IN INDUSTRY: A GUIDE FOR UNIVERSITY-INDUSTRY COLLABORATION - Ozdemir, Yavuz; Yigit, Ugur; Ozdemir, Sahika (IATED-INT ASSOC TECHNOLOGY EDUCATION & DEVELOPMENT, 2017)
One of the most important conditions for surviving and growing in today's changing and developing economic conditions is to achieve success in exports. It is one of the most basic conditions for being a global brand and in this scope companies need to follow an export-oriented policy and achieve success at this point. The ability of governments to maintain stability in the global economy depends on the success of large and multinational firms that have driven their economies on the international platform. In developing economies, firms can achieve this success only with government-backed programs. In this context, with the government-sponsored Turquality program, companies can find incentives for their growth. The term Turquality, a combine of Turkish and Quality words, is the world's first state-sponsored branding program. Today, increasingly competitive conditions and changing patterns of consumption, encourage companies seeking to take part in the market share in the international arena to create strong brands that mean more added value and greater market share. In terms of competitive sectors such as textile and ready-to-wear, automotive, electronics and food, the importance of branding in exports is increasing day by day. Turquality is a support platform created by Turkey to have a competitive advantage and to be a global player with its own brands in the international markets by providing managerial knowledge, institutionalization and developments, covering the whole processes from marketing to production, from sales to after sales services of companies with potential for branding. In this paper, the content of this program will be studied and also projects carried out within the scope of Turquality, the parts included in the prepared business plan and the applications belonging to these parts are included. This study will be a guide for both the Turkish industry and the international industry who are interested in qualitatively producing and increasing the market share.
Keywords: Turquality; university-industry collaboration; business plan; Turkish industry; Education & Educational Research